Autophagy‐dependent crosstalk between GILT and PAX‐3 influences radiation sensitivity of human melanoma cells. Issue 2 (18th October 2017) - Hathaway‐Schrader, Jessica D.; Doonan, Bently P.; Hossain, Azim; Radwan, Faisal F.Y.; Zhang, Lixia; Haque, Azizul
Abstract: Melanoma represents an ever‐increasing problem in the western world as incidence rates continue to climb. Though manageable during early stages, late stage metastatic disease is highly resistant to current intervention. We have previously shown that gamma‐interferon‐inducible lysosomal thiol‐reductase (GILT) enhances HLA class II antigen processing and immune detection of human melanoma cells. Here we report that GILT expression inhibits a potential target, paired box‐3 (PAX‐3) protein, in late stage human metastatic melanoma. We also show that GILT transfection or induction by IFN‐γ, decreases PAX‐3 protein expression while upregulating the expression of Daxx, which is also a repressor of PAX‐3. Confocal microscopic analysis demonstrated that GILT co‐localizes with PAX‐3 protein, but not with Daxx within melanoma cells. Immunoprecipitation and immunoblotting studies suggest that GILT expression negatively regulates PAX‐3 through the autophagy pathway, potentially resulting in increased susceptibility to conventional treatment in the form of chemotherapy or radiotherapy. While high‐dose radiation is a common treatment for melanoma patients, our data suggest that GILT expression significantly increased the susceptibility of melanoma cells to low‐dose radiation therapy via upregulation of tumor suppressor protein p53. Overall, these data suggest that GILT has multiple roles in inducing human melanoma cells as better targets for radiation and immunotherapy. Abstract : Melanoma represents an ever increasing problem in the western world as incidence rates continue to climb. Though manageable during early stages, late stage metastatic disease is highly resistant to current intervention. Here we show that the expression of a thiol reductase (GILT) inhibits a potential tumorigenic molecule, paired box‐3 (PAX‐3), in late stage human metastatic melanoma, and increases the susceptibility of melanoma cells to low‐dose radiation therapy via upregulation of p53.